2004
DOI: 10.1007/bf02872396
|View full text |Cite
|
Sign up to set email alerts
|

Serum dehydroepiandrosterone and lipid peroxides in human volunteers of different age groups

Abstract: The objective of the present study was to evaluate the changes in serum dehydroepiandrosterone (DHEA) and lipid peroxide levels dudng ageing in human subjects. Random blood samples were collected from a total of 128 apparently normal human volunteers of both sexes, whose age ranged between 21-70 years. The subjects were divided into groups of a decade years of age difference.Serum levels of dehydroepiandrosterone (DHEA), lipid peroxides as malondialdehyde (MDA), and insulin were analysed in all the subjects re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…36 Recently, it has been shown that serum MDA levels increase with age in the 40-50 age group but remain constant after age 50. 37 In the present study, we found no correlation between age and MDA levels. All of our subjects were healthy women over age 50.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…36 Recently, it has been shown that serum MDA levels increase with age in the 40-50 age group but remain constant after age 50. 37 In the present study, we found no correlation between age and MDA levels. All of our subjects were healthy women over age 50.…”
Section: Discussioncontrasting
confidence: 72%
“…The effect of the aging process on serum MDA and dehydroepiandrosterone (DHEA) levels has also been assessed. Sreeramulu et al 37 reported that serum MDA and DHEA levels in women are lower than those in men. They also observed a negative correlation between age and serum DHEA levels but a positive correlation between age and MDA levels.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, peroxide values are correlated positively with age. 17,39,40 Because these vitamins, mainly vitamin E and b-carotene, are antioxidants, 11 it is believed that older dairy cows have significantly lower serum concentrations of fat-soluble vitamins because of increased oxidation of these compounds. In a recent study of dairy cows during the periparturient period, LeBlanc et al 5 found that serum bcarotene and vitamin A concentrations were not significantly affected by age.…”
Section: Discussionmentioning
confidence: 99%